Microsatellite evidence for low genetic diversity and reproductive isolation in tetraploid Centaurea seridis (Asteraceae) coexisting with diploid Centaurea aspera and triploid hybrids in contact zones. (12th August 2014) - Ferriol, María; Merle, Hugo; Garmendia, Alfonso
<x xml:space="preserve">Abstract</x> Survival of polyploids in nature depends on several factors, including competition from diploid relatives and increased genetic diversity. Unlike other reported Centaurea polyploid complexes, diploid Centaurea aspera and tetraploid Centaurea seridis coexist in hybrid zones with frequent triploid individuals. The polyploid origin of C. seridis, the genetic diversity and population structure of the three cytotypes, and the degree of genetic differentiation among them were analyzed in seven mixed‐ploidy zones, involving different subspecies and ecological conditions. Ploidy was determined by flow cytometry. Microsatellite data suggested an allopolyploid origin of C. seridis. In the contact zones, diploids and tetraploids were genetically differentiated. When compared with the related C. aspera, a low genetic diversity was observed in C. seridis, which is uncommon in tetraploids. Furthermore, although diploid individuals were grouped in a single widespread genetic cluster, tetraploids were grouped in two highly differentiated clusters and showed significant isolation by distance. This genetic pattern in C. seridis may be related to a minimal gene flow with diploid relatives and/or other genetic factors, such as rare polyploidization events, founder effects or an increased selfing rate. Neither taxonomic assignment at subspecies level, nor ecological conditions could explain the genetic differentiation between tetraploid clusters. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 176, 82–98.